If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3.14 + x Solving 7 = 3.14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + -1x = 3.14 + x + -1x Combine like terms: x + -1x = 0 7 + -1x = 3.14 + 0 7 + -1x = 3.14 Add '-7' to each side of the equation. 7 + -7 + -1x = 3.14 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 3.14 + -7 -1x = 3.14 + -7 Combine like terms: 3.14 + -7 = -3.86 -1x = -3.86 Divide each side by '-1'. x = 3.86 Simplifying x = 3.86
| 7=3.14 | | 7x^3+20x^2-32x=0 | | 208-3x=(x+1)+(x+2)+(x+3)+(x+4)-50 | | 8x+8=5x+5 | | 12x+8=90 | | 3+x=3-x | | 9x=15+3x | | 3y+15=4y-20 | | 2x+3(4x+2)=34 | | 28=6g-8 | | 2x-20=x/2+10 | | 48x^3-12x^2-6x=0 | | 54-2x=10x-18 | | 7-(2x-8)=5-3x | | 2x^2=-2x+5 | | 2x=x/2+10 | | 10x+5x-2x=69 | | 208-3x=x+(x+1)+(x+2)+(x+3)+(x+4)-50 | | 3x+36=10x-48 | | y=25x-7 | | x^4+4x^3+1=0 | | 8(m-1)-7(m+3)=-29 | | 3x+108=9x-12 | | -5x-3(-x+1)=7 | | N+6=-44 | | 107-7x=29x+23 | | 2x/4=6*3 | | 150-5x=22x+18 | | -6x-6(-4x-11)=12 | | 12x^2-40=17x | | (x-7)=(x+3) | | y=-4(-2)-5 |